2000
DOI: 10.1111/j.1601-0825.2000.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin expression in oral hairy leukoplakia and normal tongue epithelium

Abstract: OBJECTIVE: To describe the expression of integrins in the epithelium of oral hairy leukoplakia (HL) and compare to that of normal lateral tongue epithelium. MATERIALS AND METHODS: Immunohistochemistry to identify integrins (α2, a α5, α6, αv, β1) was performed, using a standard biotin‐streptavidin‐peroxidase technique on five clinically and histologically confirmed frozen biopsy specimens of HL and five normal lateral tongue control tissues. RESULTS: Expression of integrins α2, α3, α6, αv, β1 was seen both in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…No histopathogenesis of the characteristic epithelial plaques in the LPC lining has been discussed in the literature, although their presence in LPC has been widely referred to (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the present observation, we demonstrated for the first time that the uppermost cells of the epithelial plaque had some basal cell characteristics based on their immunohistochemical positivities for CK19 and integrin β1, which were usually found in the basal cells of the oral squamous epithelia (15)(16)(17)(18). This finding might be important for speculating how epithelial plaque is generated.…”
Section: Discussionsupporting
confidence: 61%
“…No histopathogenesis of the characteristic epithelial plaques in the LPC lining has been discussed in the literature, although their presence in LPC has been widely referred to (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In the present observation, we demonstrated for the first time that the uppermost cells of the epithelial plaque had some basal cell characteristics based on their immunohistochemical positivities for CK19 and integrin β1, which were usually found in the basal cells of the oral squamous epithelia (15)(16)(17)(18). This finding might be important for speculating how epithelial plaque is generated.…”
Section: Discussionsupporting
confidence: 61%
“…Integrins α1β1, α2β1, α3β1, α6β1, α9β1, and α6β4 are collagen‐binding integrins in healthy epithelia, of those only α1β1 and α2β1 bind collagen directly due to a presence of I‐domain in the alpha subunit. αvβ1, α5β1, αvβ5, and αvβ6 are oral epithelia, fibronectin‐binding integrins 27–29. When examining cell adhesion, we have found that nm23‐H1‐overexpressing cells tend to be different from the control cells only in the early adhesion process (90 min), while 24 h after seeding the examined differences are negligible.…”
Section: Discussionmentioning
confidence: 81%